Visual Perception and Visuomotor Reaction Speed Are Independent of the Individual Alpha Frequency - Hülsdünker, Thorben; Mierau, Andreas (Frontiers in Neuroscience, 2021)
While the resting-state individual alpha frequency (IAF) is related to cognitive performance and the temporal resolution of visual perception, it remains unclear how it affects neural correlates of visual perception and reaction processes. This study aimed to unravel the relation between IAF, visual perception and visual-motor reaction time. 148 participants (28 non-athletes, 39 table tennis players, 81 badminton players) investigated in three previous studies were considered. During a visuomotor reaction task, visuomotor reaction time (VMRT), EMG onset were determined. In addition, a 64-channel EEG system identified the N2, N2-r and BA6 negativity potentials representing visual and motor processes related to visuomotor reactions. Resting-state individual alpha frequency (IAF) in visual and motor regions was compared based on sport experience (athletes vs. non-athletes), discipline (badminton vs. table tennis), reaction performance (fast vs. medium vs. slow reaction time). Further, differences in IAF were determined in relation to the speed of neural visual (high vs. medium vs. low N2/N2-r latency) and motor high vs. medium vs. low BA6 negativity latency). Group comparisons did not reveal any difference in IAF between athletes and non-athletes (p=0.352, ηp2=0.02) or badminton and table tennis players (p=0.221, ηp2=0.02). Similarly, classification based on behavioral or neural performance indicators did not reveal any effects on IAF (p≥0.158, ηp2≤0.027). IAF was not correlated to any of the behavioral or neural parameters (r≤0.10, p≥0.221). In contrast to behavioral results on cognitive performance and visual temporal resolution, the resting state IAF seemed unrelated to neural correlates of visual perception and visuomotor speed in simple reaction tasks. Considering previous results on correlations between IAF, cognitive abilities and temporal sampling of visual information, the results suggest a higher IAF may facilitate the amount and frequency but not the speed of information transfer.